High‐Performance Compressible Zinc Ion Battery Based on Melamine Foam‐Derived Electrodes. Issue 8 (17th May 2022) - Li, Danting; Lv, Tian; Chen, Zilin; Yang, Yunlong; Liu, Yanan; Wan, Jun; Qi, Yunlong; Cao, Shaokui; Chen, Tao
Abstract : Zinc ion batteries (ZIBs) with high capacity and superior safeness represent a promising candidate as the power source for portable electronics. However, it remains a big challenge to construct high‐performance ZIBs with highly compressible capability, due to the limited compressible properties of electrodes and electrolyte. Herein, a highly compressible ZIB using a cathode of polyaniline/carbon foam (PANI/CF), an anode of Zn/CF, and a gel electrolyte containing polyvinyl alcohol and Zn(CF3 SO3 )2 is demonstrated. The 3D interconnection structure of the self‐supporting CF material not only can provide compressible platform to load active materials, but also can facilitate transport of ions. As desired, the newly developed ZIB exhibits high specific capacity of 215 mAh g −1 at a current density of 1 A g −1 and excellent cyclic stability (88% after 2500 charge/discharge cycles). Benefiting from the excellent mechanical compressibility and stability of CFs, the ZIBs well maintain their original electrochemical performance under a compressive strain as high as 75% and even pressing/releasing for 1000 cycles under a strain of 60%, indicating outstanding compressible capability. The compressible ZIB represents a promising candidate to be used as power supplies for portable electronics in the near future. Abstract : A facile approach is developed to fabricate a highly compressible 3D cathode and anode based on low‐cost commercial melamine foam. Ascribed to their unique structure, the developed zinc‐ion batteries not only show high electrochemical performance and cyclic stability, but also exhibit excellent compressible property and mechanical stability.